Critical Discourse Analysis on “Bright: An English” Textbook: Gender Equity in a Popular EFL School Textbook in Indonesia - Apsari, Andi Aspian Nur; Hidayat, Didin Nuruddin; Husna, Nida; Alek, Alek (Elsya : Journal of English Language Studies, 2022)
Using Critical Discourse Analysis as an analysis tool, this study explores gender representation in the national EFL textbook “Bright: An English” for Eighth Grade Junior High School students, a book utilized in Al-Ikhlas Lambuya Junior High School’s learning and teaching process. Fairclough's three-dimensional framework was used to examine the data in this study. The study aims to see how gender roles are communicated and how gender equity is reflected in the textbook. To uncover the power imbalance or disparity between males and females, characteristics such as male and female visual representation, male and female characters, male and female social, domestic duties, male and female semantic roles, and activities were investigated. The research revealed a gender bias in favour of men in particular functions and activities, such as becoming an 'athlete,' engaging in social events, and participating in sports. On the other hand, female dominance is evident in that female students outnumber male students significantly. Nevertheless, the study discovered some equality in terms of pictorial representation, some activities, and roles. Although conventional roles and behaviours are associated with female and male genders in this book, all genders are equally portrayed in terms of social position, power, and domination. Furthermore, no ideology such as anti-feminism or masculinity is discussed in this text.